The Influence of Leadership Style, Work Motivation and Loyalty on Supermarket Employee Performance: Pengaruh Gaya Kepemimpinan, Motivasi Kerja dan Loyalitas Terhadap Kinerja Karyawan Supermarket - Fitrianti, Fita; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the influence of leadership style on employee performance, the effect of work motivation on employee performance, the effect of loyalty on employee performance, and the simultaneous influence of leadership style, work motivation, and loyalty on employee performance at Alfamart Buduran branch. This research is a type of quantitative research. The population used is all Alfamart employees, totaling 40 employees. Data collection techniques using questionnaires. The data analysis technique used was classical assumption test, multiple linear regression and hypothesis testing. This study concludes that leadership style has an effect and is significant on employee performance, while work motivation has no effect and is not significant on employee performance, and loyalty has an effect on employee performance. And simultaneously Leadership Style, Work Motivation and Loyalty affect the Employee Performance of Alfamart Buduran branch.